Mathematical structure of the Strumok stream cipher - Kuznetsov, O.O.; Gorbenko, I.D.; Gorbenko, Y.I.; Alekseychuk, A.M.; Tymchenko, V.A. (Radiotekhnika, 2018)
The main development results of a new keystream generator, named “Strumok”, and offered as a candidate for the national symmetric encryption standard of Ukraine, are presented. Strumok is built according to the SNOW2.0-like schema of the summation generator; increased secret key length and the initialization vector allow using reliably the stream cipher even taking into account quantum cryptographic analysis methods. The basic transformations and individual results from the cipher performance research are given, moreover, here it is shown the generator, capable of forming a keystream at speed exceeding 10 Gbit per sec.